1999
DOI: 10.1073/pnas.96.25.14470
|View full text |Cite
|
Sign up to set email alerts
|

CTACK, a skin-associated chemokine that preferentially attracts skin-homing memory T cells

Abstract: In contrast to naive lymphocytes, memory͞effector lymphocytes can access nonlymphoid effector sites and display restricted, often tissue-selective, migration behavior. The cutaneous lymphocyteassociated antigen (CLA) defines a subset of circulating memory T cells that selectively localize in cutaneous sites mediated in part by the interaction of CLA with its vascular ligand E-selectin. Here, we report the identification and characterization of a CC chemokine, cutaneous T cell-attracting chemokine (CTACK). Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
386
1
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 468 publications
(403 citation statements)
references
References 31 publications
11
386
1
5
Order By: Relevance
“…A recent report concluded that the only CCL27-responsive cells in human peripheral blood were CLA ϩ memory CD4 and CD8 T cells (9). These CCR10 Abs were used in conjunction with lineage-specific Abs to investigate CCR10 expression by different blood-derived cells to confirm and extend this observation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…A recent report concluded that the only CCL27-responsive cells in human peripheral blood were CLA ϩ memory CD4 and CD8 T cells (9). These CCR10 Abs were used in conjunction with lineage-specific Abs to investigate CCR10 expression by different blood-derived cells to confirm and extend this observation.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, it was postulated that a skin-specific activation cue (step 2) or chemoattractant (step 4) might confer skin-specific homing to the CLA ϩ T cell population or to a subset of cells within this population. CCL27 is the only skin-specific chemokine known (9) and by interacting with CLA ϩ /CCR10 ϩ memory T cells, it may provide the postulated skin-specific step that facilitates these cells' entry into cutaneous sites.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, gene targeting has also revealed unequivocally a role for CCR6 in the regulation of DC traffic in the mucosal compartment. CCL17/TARC and CCL27/CTAK are important for the traffic of skin homing T lymphocytes (55,56). CCL17/TARC recruits CLA + T cells, which are the predominant type present in the skin.…”
Section: Polarized Responsesmentioning
confidence: 99%
“…Constitutively expressed chemokines act in primary and secondary lymphoid organs [16,17,26] and peripheral tissues [27,28]. The CCR7 ligands, CCL19 and CCL21 [29,30], are expressed in the T-cell area of secondary lymphoid organs as well as on high endothelial venules (HEV) [31] and orchestrate the migration of CCR7 1 cells.…”
mentioning
confidence: 99%